1968
DOI: 10.1029/ja073i017p05733
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the magnetopause at 6.6REin terms of 50- to 150-keV electrons

Abstract: Measurements were made with a magnetic deflection electron spectrometer of electrons in the range 50–150 kev at the boundary of the magnetosphere on January 14, 1967. At this time, the magnetopause was compressed inside the orbit of the ATS 1 geostationary satellite, which was located at 6.6 RE in the subsolar region of the magnetosphere. The first crossing of the trapping boundary and magnetic field reversal was followed by many transient count rate increases and magnetic field variations. Owing to the rapid … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1970
1970
1992
1992

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…Previous studies suggested that the magnetopause may be severely distorted when it is compressed to unusually low altitudes [Lezniak and Winckler, 1968;Skillman and Sugiura, 1971]. For this reason we have searched for unusual magnetopause distortions during the August 4, 1972, events.…”
Section: Magnetopause Normals and Distortionsmentioning
confidence: 99%
“…Previous studies suggested that the magnetopause may be severely distorted when it is compressed to unusually low altitudes [Lezniak and Winckler, 1968;Skillman and Sugiura, 1971]. For this reason we have searched for unusual magnetopause distortions during the August 4, 1972, events.…”
Section: Magnetopause Normals and Distortionsmentioning
confidence: 99%
“…Since the first spacecraft observations of the noon magnetopause near t0 RE, it has been clear that this solar windmagnetosphere boundary is frequently in motion under the fluctuating pressure of the solar wind [Sonnet et al, 1960;Cahill and Amazeen, 1963;Cahill and Patel, 1967;Kaufmann and Konradi, 1969;Aubry et al, 1971]. There have been occasional observations at distances much closer than t0 RE, usually associated with magnetic storms [Cummings and Coleman, 1968; Lezniak and Winckler, 1968;Skillman and Sugiura, 1971]. Most of such observations have been by geosynchronous (6.6 R E circular orbit) satellites, since such satellites spend half their time in the outer dayside magnetosphere at an ideal location to observe inward motion of the magnetopause [Russell, 1976;Rufenach et al, 1989].…”
Section: Introductionmentioning
confidence: 99%
“…The day side magnetopause forms a boundary that both confines the geomagnetically trapped particles and prevents the penetration of the solar wind ions and electrons into the magnetosphere [Freeman et al, 1963;Freeman, 1964;Anderson et al, 1965;Frank, 1965;Lezniak and Winckler, 1968;Vasyliunas, 1968a, b;Singer and Bame, 1970]. Imp 3 particle measurements have shown the existence of a permanent layer of electrons having energy greater than 40 keV.…”
Section: Introductionmentioning
confidence: 99%